Multi-generational exposure of Daphnia magna to pharmaceuticals: Effects on colonization, reproduction, and habitat selection behavior - María Pilar González; Ilaria Cecconi; David Salvatierra; María Úbeda-Manzanaro; Gema Parra; Eloísa Ramos-Rodríguez; Cristiano V.M. Araújo (Ecotoxicology and Environmental Safety)
The presence of pharmaceuticals in the aquatic environment is increasing due to their growing use for human health. Although most studies are based on short exposures to these contaminants, the present study has emerged from the need to study pharmaceuticals in aquatic organisms over a long-term exposure to understand any multi-generational chronic effects and alterations regarding habitat selection. Therefore, this study shows: (1) the ability of Daphnia magna to colonize environments contaminated with caffeine, ibuprofen and fluoxetine, and (2) the effect of these pharmaceuticals on reproduction and habitat selection (under two scenarios: with and without food) after a long-term exposure period of three generations. It was observed that caffeine shortened the time between generations and caused an increase in the number of neonates per female. The opposite was observed with ibuprofen: the time to reach the third F3 generation was double when compared to those exposed to caffeine. Fluoxetine did not alter the reproduction, nor was repellent/attractive for daphnids. In the habitat selection tests, organisms cultivated in clean water preferred the compartment with caffeine, highlighting its attractive effect. Caffeine was also attractive for daphnids in the colonization test. Apart from this, no chemical showed any attractive or repulsive effect in the absence of food during the habitat selection tests. Our findings show that the presence of some pharmaceuticals could cause alterations in distribution and habitat selection patterns, and a significant effect on the reproduction of this species. underlining the importance of studying the effects of contamination by long-term exposure.